From farm to ship to fork: The role of maritime insurance in facilitating global food trade - Denamiel, Thibault; Dodd, Emma; Glauber, Joseph W.; Reinsch, William Alan; Welsh, Caitlin (Center for Strategic and International Studies, 2024)
Developments in agriculture and transportation over the last century have shifted global diets from traditional to staple crops, largely concentrating the source of populations’ nutritional and caloric needs to a limited number of producing countries. Three staple crops—rice, corn, and wheat—now provide more than 40 percent of global caloric intake. The remaining dietary needs of populations are in part met by local markets, but the outsourcing of a significant proportion of food production is now a permanent fixture of food security and nutrition in a globalized agricultural marketplace. More than 80 percent of global trade in staple crops and oilseeds relies on a handful of maritime trade routes that, when disrupted, create a chokehold on food supplies.